2004
DOI: 10.1177/10634266040120010101
|View full text |Cite
|
Sign up to set email alerts
|

The Prevention of Violent Behavior by Chronic and Serious Male Juvenile Offenders

Abstract: Over the past several decades, an increasing number of youth have been incarcerated for violent offenses. Existing interventions for serious offenders target the prevention of subsequent delinquent behavior in general, rather than the prevention of violent behavior in particular. Within the context of a randomized clinical trial of 79 adolescent males involved in the juvenile justice system, we examine the ability of multidimensional treatment foster care (MTFC) to prevent subsequent violent offending relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 13 publications
1
66
0
Order By: Relevance
“…Findings suggest that some youth may benefit from intensive and comprehensive service models, such as Multidimensional Treatment Foster Care, Multisystemic Therapy, or Intensive Case Management-programs that have demonstrated long-term effectiveness with very at-risk adolescent populations that overlap with foster care (Cauce et al 1994;Chamberlain et al 2007;Eddy et al 2004;Henggeler et al 1997). Other youths may gain from a different set of services, including mentoring, tuition assistance, or employment training.…”
Section: Discussionmentioning
confidence: 94%
“…Findings suggest that some youth may benefit from intensive and comprehensive service models, such as Multidimensional Treatment Foster Care, Multisystemic Therapy, or Intensive Case Management-programs that have demonstrated long-term effectiveness with very at-risk adolescent populations that overlap with foster care (Cauce et al 1994;Chamberlain et al 2007;Eddy et al 2004;Henggeler et al 1997). Other youths may gain from a different set of services, including mentoring, tuition assistance, or employment training.…”
Section: Discussionmentioning
confidence: 94%
“…In the first trial, Chamberlain found that MTFC boys had significantly lower rates of official and selfreported delinquency in a 12-month follow-up and lower rates of violent offending in a 24-month follow-up than did group care youth (Chamberlain & Reid, 1998;Eddy, Whaley, & Chamberlain, 2004). A second trial began in 1996 to examine the efficacy of MTFC with an adolescent female population.…”
Section: Summary Of Prior Work On the Mtfc Modelmentioning
confidence: 99%
“…Past studies have indicated that MTFC is an effective treatment approach for delinquent boys, producing outcomes superior to GC in terms of arrest and incarceration rates (Chamberlain & Reid, 1998;Eddy, Whaley, & Chamberlain, 2004). In addition, the cost effectiveness of MTFC relative to GC for boys was evaluated in an independent economic evaluation where long-term cost savings to taxpayers was estimated to range from $21,836 to $87,622 per youth (Aos, Phipps, Barnoski, & Leib, 2001).…”
mentioning
confidence: 99%